Culturological orientators of modern Ukrainian cinema critics - T. G. Kokhan (Ukrainian Cultural Studies, 2020)
The article analyses the position of Ukrainian scientists, represented in their works during the first two decades of the XXI century, when the influence of the basis of the cultural analyses on the development of cinema critics has become appreciable. The accent has been made on new approaches both to the history of Ukrainian cinema in trying to understand personalized approach prevails and to the estimation of subject direction of the films shoot on the boundary of the XX – XXI centuries. It is underlined that film expert’s attention was concentrated on the further improvement of notion-categorical apparatus which provides investigations in film critics. It is shown that film science outlines some human problems which having historical cultural traditions, can appear as aesthetical-artistic reference points in creative process. It is declared that the important aspect of the article is dedicated to the fixation of the art studies formation history in the process of cinema development. The role of Danish producer Urban Gad, the author of the book "Cinema, its means and aims" is marked. It is indicated that while constantly shooting films U.Gad summarized his own experience of work in the cinema making in the first European investigation in the cinema studies. It is underlined that taking into consideration the dynamics of cinematograph’s development, using of historical and cultural achievements of the past as reference points for modern cinema theory demands caution and correctness. In the context of this thesis systematization and analysis of works of Ukrainian film critics on the activities of national cinematograph’s development are presented both actual and expediency. It is shown that using in the cinema study fundamental principles of cultural analysis in particular cross-scientific personalization a composed element of biographic method – to correlate cinema analysis with material of such human sciences as aesthetics, ethics and psychology. It is noticed that taking into consideration collective character of the creation in cinematograph the principle of personalization objectively appraises the contribution of each representative of the cinematic group within the creative process.